THE USE OF COMPOST Chromolaena odorata TO IMPROVE SOIL POTASSIUM - Rani Saimara Putri; Arthur G. Pinaria (Jurnal Agroekoteknologi Terapan, 2021)
The needs of the agricultural products in large quantity and quality demands increased attention to the management of the nutrient Potassium. This is because Potassium is the most absorbed of food crops, especially cereal crops such as rice and corn are the increase of productivity or production continues to be encouraged. Based on data from the nutrient uptake of Potassium, to achieve the productivity of paddy rice, corn, cassava, and soybean respectively to 4.7 t, the 2.7 t, the 12.2 t, and 1.2 t/ha, nutrient Potassium is absorbed in a row 122,4 kg, of 49.7 kg, to 76.0 kg, and 25.6 kg/ ha. This value is equivalent to 235,4 kg, to 95.7 kg, 146,3 kg and to 49.3 kg KCl/ha. Potassium is an essential nutrient needed by plants in large quantities, even to the plants of rice and cassava exceed the needs of N.Keywords:  corn; compost. Abstrak                             Kebutuhan produk pertanian dalam jumlah besar dan berkualitas menuntut peningkatan perhatian terhadap pengelolaan hara Kalium. Hal ini karena Kalium paling banyak diserap tanaman pangan, terutama tanaman serealia seperti padi dan jagung yang peningkatan produktivitas atau produksinya terus dipacu. Berdasarkan data serapan hara Kalium, untuk mencapai produktivitas padi sawah, jagung, ubi kayu, dan kedelai masing-masing 4,7 t, 2,7 t, 12,2 t, dan 1,2 t/ha. Hara Kalium yang terserap berturut-turut 122,4 kg, 49,7 kg, 76,0 kg, dan 25,6 kg/ ha. Nilai ini setara dengan 235,4 kg, 95,7 kg, 146,3 kg, dan 49,3 kg KCl/ha. Kalium sebagai hara esensial dibutuhkan tanaman dalam jumlah banyak dan bahkan untuk tanaman padi dan ubi kayu melebihi kebutuhan N. Kata kunci: jagung; kompos.